Project-Based Learning with Paired Expert and Beginner Models to Develop Innovative Thinking Skills - Mashfufah, Aynin; Rufiana, Intan Sari; Arifin, Slamet; Ekawati, Ratna; Sari, Dian Ratna; Salam, Haerul (Universitas Pendidikan Ganesha, 2024)
Students in the Master of Basic Education program have diverse backgrounds. However, innovative abilities have not grown because teaching experience has not been accompanied by experience using technology and vice versa. This study aims to develop students' innovative thinking skills through a learning model that is project-based learning with a paired novice expert model. This type of research is pre-experimental design with a sample of 38 Master of Basic Education students. Questionnaire filling was used to assess students' perspectives on innovative thinking skills before and after treatment and an assessment rubric to assess the product. Data from the questionnaire was analyzed using the Wilcoxon test and the resulting product was analyzed descriptively quantitatively. Based on the results of data analysis, it can be concluded that innovative thinking skills can be developed. Teamwork is an aspect that has improved very well compared to the other four aspects of innovative thinking skills. The results of project completion show that on average, innovative thinking skills have developed well. The contextualized learning environment by presenting real problems related to the learning process of students in elementary schools is able to stimulate students' ability to solve problems. Problem solving is also done well because the diverse backgrounds of individuals in the group contribute to each other and work well together.